Canada in the European Age, 1453-1919 - Naylor, R. T. (MQUP, 2006)
As Bruce Trigger explains in his preface, Canada in the European Age, 1453-1919 was the first history in which native peoples appeared as genuine actors in human dramas - mainly tragedies - instead of as part of the flora and fauna in the background. By stressing the interconnections between the grand events of the conquest and subjegation of the globe by European empire builders and the less dramatic events in Canada, Naylor's book led to a fundamental reinterpretation of Canadian social, economic, and political history.